P123The rescue of Ca2+ cycling abnormalities conferred by HCM-causing mutations with analogues of the green tea polyphenol epigallocatechin-3-gallate. (15th July 2014) - Robinson, P; Liu, X; Zhang, Y-H; Khandelwal, A; Blagg, B; Casadei, B; Watkins, H; Redwood, C
Abstract: Mutations in thin filament regulatory proteins that cause hypertrophic cardiomyopathy (HCM) confer distinct primary alterations of cardiac contractility. We have shown that altered Ca2+-buffering by mutant thin filaments leads to altered Ca2+ handling and results in stimulation of Ca2+-dependent signalling pathways. To do this we have used adenoviral mediated expression of cTnT R92Q, cTnI R145G and α-TM D175N in adult guinea pig cardiomyocytes at a ratio of 1:1 with the endogenous protein. Simultaneous measurement of unloaded sarcomere-shortening and Ca2+ transients using fura-2 loading, showed the HCM mutations caused a significant decrease in the basal sarcomere length coupled with an increase in the diastolic Ca2+ concentration. The mechanism of alterations to EC-coupling was also investigated using tetracaine and caffeine challenging combined with simultaneous whole cell patch clamping. HCM mutant cells displayed reduced SR load ( 1.4fold), slowed NCX calcium extrusion ( 2.5fold), unchanged SERCA2 activity, increased ryanodine receptor leak ( 5fold) and increased calcium buffering ( 3fold). This was coupled to an increase in Ca2+ dependent NFAT nuclear localisation. Further studies using the green tea catechin, epigallocatechin gallate (EGCg) and sister compound epicatechin-3-gallate (ECG), have shown that the compounds can partiality reverse the increase in diastolic Ca2+ observed in cardiomyocytes containing HCM causing mutations. The mechanism is thought to be via an interaction with cTnC (measured using intrinsic cTnC tyrosine fluorescence) which in turn causes a reduction of in vitro thin filament Ca2+ affinity (measured using cTnC labelled with IAANS fluorophore at Cys 35). Data acquired so far suggests that catechins and their derivative compounds may provide a possible therapeutic approach for correcting Ca2+ regulation and Ca2+ dependent remodelling in HCM. We have recently obtained library of 37 EGCg analogues which we have screened for cTnC affinity and thin filament Ca2+ affinity. We have now identified several catechins with potentially greater efficacy than the parent compound, and plan to test their ability to rescue the cellular HCM phenotype characterised above.